Analisis Perbedaan Kinerja Keuangan Sebelum dan Sesudah Penerapan Prinsip Good Corporate Governance Pada PT. Petrokimia Gresik - Perwita Sari, Rida (Jurnal Riset Ekonomi dan Bisnis, 2009)
This study aimed to know the process of implementing the principles of Good Corporate Governance (GCG) in by the company and to know the difference in financial performance before and after implementation of the principles of GCG at PT. Petrokimia Gresik (PT. PKG). This research was conducted by using data taken from financial statements in 2003 and 2005 in PT. PKG is then processed by using statistical analysis as a tool to test the hypothesis raised by the researcher that is using "Paired Samples T-test" which is a test performed on two sample pairs. Based on the results of the analysis “Paired Samples T-test" can be concluded that the measurement of financial performance used is based Keputusan Menteri BUMN Nomor Kep.100/M. BUMN/2002: Return On Equity (ROE), Return On Investment (ROI), Cash Ratio, Current Ratio, Collection periods (CP), Inventory Turnover (PP), Turnover Total Asset/Total Asset Turn Over (TATO), and the ratio of Total Equity to Total Assets. Seven indicators of financial performance is ROE, ROI, Cash Ratio, Current Ratio, CP, PP, and TATO is no difference between the financial performance before and after implementation of the principles of GCG at the PT. PKG, while financial performance indicators measured by the ratio of Total Equity to Total Assets has shown there are differences between the financial performance before and after implementation of the principles of GCG in by the company.Keywords: Good Corporate Governance, Financial Performance